2000
DOI: 10.1093/intimm/12.11.1623
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T lymphocytes as a primary cellular target for BAT mAb stimulation

Abstract: BAT is a monoclonal antibody (mAb) produced against membranes of a human Burkitt lymphoma cell line (Daudi) that was selected for its ability to stimulate lymphocyte proliferation. BAT manifests anti-tumor properties in mice bearing a variety of murine tumors. BAT also induced regression of human tumors inoculated into SCID mice that had been engrafted with human lymphocytes. The anti-tumor activity of BAT was related to its immune stimulatory properties. Previous data indicated that T lymphocytes and NK cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Autologous T cells were purified from nonadherent fraction of the buffy coat that was used to purify MDM, using nylon wool column as described earlier (22). In brief, the nonadherent cells were incubated in prewashed nylon wool at 37°C in 5% CO 2 .…”
Section: T Cell Activation Assaymentioning
confidence: 99%
“…Autologous T cells were purified from nonadherent fraction of the buffy coat that was used to purify MDM, using nylon wool column as described earlier (22). In brief, the nonadherent cells were incubated in prewashed nylon wool at 37°C in 5% CO 2 .…”
Section: T Cell Activation Assaymentioning
confidence: 99%
“…Another mechanism by which tumors inhibit anti-tumor immunity is through the induction of Treg cells. Treg cells are inhibitory CD4 1 T cells that are increased in cancer patients, both peripherally and in tumors, and can form a barrier to eliciting effective immune responses [17][18][19][20][21][22]. It has been shown that anti-tumor immunity is enhanced by depletion of Treg cells with agents such as anti-CD25 and low-dose CPM [23][24][25][40][41][42].…”
Section: Pdl-1 Expression On Human Tumor Cells and The Number Of Tumomentioning
confidence: 99%
“…Treg cells are inhibitory CD4 1 T cells that are increased in cancer patients and can potentially form a barrier to eliciting effective immune response [17][18][19][20][21][22]. Not surprisingly, the inactivation or depletion of Treg cells has been actively pursued, in order to develop more potent anti-tumor immunotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of BAT determined that NK or T cells mediated the antitumor effect of BAT [35] and the primary cellular target for BAT in human peripheral blood cells were CD4 + T cells that stimulated the secretion of IFN-γ [40]. The local secretion of IFN-γ induces an anti-tumor response by recruitment of host immune cells to the tumor resulting in a successful host anti-tumor immune response.…”
Section: The Use Of Antibodies In Cancer Therapymentioning
confidence: 99%